(untitled) (American Journal of Life Science and Innovation, 2025)
Effective communication skills in young children encompass a diverse range of abilities crucial for early autism spectrum disorder (ASD) identification. This study aims to analyse communication skills in 36 preschool children (ages 1.6 to 4.6 years) diagnosed with autism in Dubai, employing the Early Communication Assessment (ECA) tool developed by Coupe O’Kane and Goldbart (1998). The ECA evaluates 13 areas of early communicative functioning categorised into 3 to 5 developmental stages, ranging from Reflexive to Intentional Conventional. Communication abilities were assessed, and the 5 ECA levels were condensed into 3 for comparative analysis. Key communicative areas, such as joint referencing, social organisation, turn-taking, and imitation, were identified as significantly delayed in this cohort. Conversely, affective behavior, audio-visual behaviors, and physical production of sound exhibited relatively lesser impact. Contrary to common assumptions, poor eye contact was not the predominant indicator of communication challenges. Comparative analyses were conducted between communication skills and perceptive cognitive abilities, language proficiency, and symbolic play. No substantial correlation was found between perceptive cognitive abilities and communication skills. However, a significant association was observed between communication abilities, language proficiency, and symbolic play. These findings underscore the complexity of early communication profiles in preschool children with ASD in Dubai, emphasising the need for comprehensive assessment and targeted interventions beyond conventional indicators.